The Endocrine Function of the Heart: Physiology and Involvements of Natriuretic Peptides and Cyclic Nucleotide Phosphodiesterases in Heart Failure - Lugnier, Claire; Meyer, Alain; Charloux, Anne; Andrès, Emmanuel; Gény, Bernard; Talha, Samy (Journal of clinical medicine, 2019)
Besides pumping, the heart participates in hydro-sodium homeostasis and systemic blood pressure regulation through its endocrine function mainly represented by the large family of natriuretic peptides (NPs), including essentially atrial natriuretic (ANP) and brain natriuretic peptides (BNP). Under normal conditions, these peptides are synthesized in response to atrial cardiomyocyte stretch, increase natriuresis, diuresis, and vascular permeability through binding of the second intracellular messenger’s guanosine 3′,5′-cyclic monophosphate (cGMP) to specific receptors. During heart failure (HF), the beneficial effects of the enhanced cardiac hormones secretion are reduced, in connection with renal resistance to NP. In addition, there is a BNP paradox characterized by a physiological inefficiency of the BNP forms assayed by current methods. In this context, it appears interesting to improve the efficiency of the cardiac natriuretic system by inhibiting cyclic nucleotide phosphodiesterases, responsible for the degradation of cGMP. Recent data support such a therapeutic approach which can improve the quality of life and the prognosis of patients with HF.